Between Tradition and Hierarchy: Language Policy in Preserving Linguistic Uniqueness in East Java Islamic Boarding Schools - Hanif Zulfa Fauziyah; Zuliati Rohmah (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This study explores the implementation of a language policy at the Al Islahiyyah Islamic Boarding School, which emphasizes the use of the Javanese language (Krama) across various levels. The policy aligns with traditional cultural practices, dividing the language into three levels: Krama Inggil, Krama Alus, and Ngoko Alus, each reflecting different degrees of respect and social hierarchy. The methodology involved qualitative analysis through observations and interviews with students and teachers to assess the application and challenges of this policy. Results indicate that the policy successfully preserves cultural heritage and fosters respect and politeness among students. However, it also presents challenges due to the diverse linguistic backgrounds of the students, many of whom are not familiar with proper Javanese usage at home. The study concludes that while the language policy contributes positively to cultural identity and linguistic proficiency, it requires significant adaptation efforts. Furthermore, the research suggests the need for future studies to examine the long-term effects of the policy on students' proficiency in other languages and its broader implications in a multilingual context. Future research should also investigate the integration of other languages into the curriculum and track the students' linguistic and cultural adaptability post-graduation to provide a comprehensive understanding of the policy's impact.